Ag‐Refined Kesterite in Superstrate Solar Cell Configuration with 9.7% Power Conversion Efficiency. (17th August 2022) - Wang, Zhuoran; Wang, Yongjie; Taghipour, Nima; Peng, Lucheng; Konstantatos, Gerasimos
Abstract: Thin‐film photovoltaic materials offer a sustainable solution to the current environmental and energy challenges, among which kesterite or Cu2 ZnSn(S, Se)4 is of particular interest due to its earth‐abundant, non‐toxic nature, and realization of rapid efficiency improvement in earlier 2010s. In contrast to the majority of research on kesterite solar cells that relies on the substrate configuration, this study is pioneering in applying superstrate configuration to tackle the surface incompatibility challenges as well as the use of Cd‐based buffer layers encountered in the substrate configuration – issues that act as barriers in the deployment of this photovoltaic technology. By applying a Ag‐refining step on an ultrathin (Cu, Ag)2 ZnSn(S, Se)4 with TiO2 buffer layer, a Cd‐free superstrate kesterite solar cell with efficiency of 9.7% – a record high efficiency in its class is reported. This refining step is crucial in increasing the ratio of Ag/(Cu+Ag) to 40%–60%, overcoming the limit of 35% set by efficient substrate devices. The promoted grain growth and improved charge transport kinetics (i.e., enhanced lifetime/extraction and reduced trap states) ultimately contribute to the boost of performance. Critical device/semiconductor characteristics reveal a majorly depleted absorber but with high density of back surface defects identified as the main limiting factor in device performance. Abstract : An ultrathin, environment‐friendly kesterite solar cell in novel superstrate configuration is fabricated with record high power conversion efficiency of 9.7%, where a Ag‐refining step is critical in increasing the ratio of Ag‐to‐Cu substitution and improving carrier transport dynamics. A high density of back surface defects is identified as the limiting factor of device performance.